Using electronic communication to bridge the research to practice gap among mentoring professionals. Issue 3 (27th May 2017) - Smith, Cindy Ann; Willox, Lara; Olds, Courtney
Abstract: The field of mentoring includes a broad base of stakeholders, such as researchers and practitioners who implement mentoring programs. The research-to-practice gap is an ongoing area of concern in many fields of social science including mentoring. One reason for this is that researchers and practitioners often operate in isolation. Technology is playing an ever-increasing role in the professional lives of practitioners and researchers, therefore, this study explored the engagement of both groups through the YOUTHMENTORING list serve; a resource provided by the University of Illinois-Chicago. Through a comprehensive qualitative study of list serve content, connections, and engagement it was found that the YOUTHMENTORING list serve promoted collaboration among stakeholders. Members found the resource to be valuable to their practice. Implications for the field and future research are discussed.